The matrix resurrections [videorecording (DVD)] - Wachowski, Lana, 1965-; Mitchell, David (Screenwriter); Hemon, Aleksandar, 1964-; Reeves, Keanu; Moss, Carrie-Anne, 1970-; Abdul-Mateen, Yahya, II, 1986-; Henwick, Jessica, 1992-; Groff, Jonathan; Chopra Jonas, Priyanka; Harris, Neil Patrick, 1973-; Ricci, Christina; Smith, Jada Pinkett, 1971- (Warner Bros. Entertainment, 2022)
"To truly know himself, Neo must follow the white rabbit once again into the Matrix ... What he doesn't know is that the Matrix is more dangerous than ever"--Container.